Enhancing Learning Motivation through a Blended Learning Model: Integrating Mobile Devices and Virtual Reality - Lu, Haixia; Ma, Lihua; Luo, Junna (International Journal of Interactive Mobile Technologies (iJIM), 2024)
With the rapid development of information technology (IT), the application of mobile devices and virtual reality (VR) in education has become increasingly widespread, giving rise to a blended learning model that integrates these two technologies. This model, through the immersive experience provided by virtual environments and the convenience of mobile devices, effectively expands the temporal and spatial dimensions of traditional learning, offering new potential for enhancing students’ learning motivation. However, existing research has predominantly focused on either mobile learning or VR in isolation, with relatively limited exploration of how the combination of these technologies within a blended learning model impacts learning motivation. Moreover, most of the current methods are constrained to simple questionnaire surveys, lacking in-depth analysis of students’ interactive behaviours and the underlying mechanisms that contribute to motivation formation. In this study, a comprehensive evaluation model was constructed based on an examination of students’ interactions in the blended learning model and its effects on learning motivation. An empirical study was then conducted to provide innovative theoretical and methodological support for educational practice.